KONTRIBUSI MATEMATIKA DALAM MENYIKAPI HAK WARIS ANAK ANGKAT BERDASARKAN PERSPEKTIF HUKUM ISLAM DAN HUKUM NEGARA - Diyah Ayu Rizki Pradita; Nur Azizah (LP2M Universitas Ibrahimy, 2023)
This study aims to describe the contribution of mathematics in the distribution of inheritance rights for adopted children based on Islamic law and state law. The research method used is descriptive qualitative. The subjects of this study are inheritance, Islamic law and state law. Then the object of this study is adopted children. The results of this study indicate that the contribution of mathematics to this inheritance right is in the calculation process that applies mathematical modeling to heirs by assuming the variables x, y and z. In addition, it also uses a systematic solution by writing down things that are known and asked, in order to facilitate the process of solving the cases presented. As for the case of the inheritance rights of adopted children, it shows that there is no special inheritance right for adopted children, but according to the compilation of Islamic law, adopted children get 1/3 of the heir's assets as a mandatory will.